Xiaomi Brand Mobile Phone Purchase Decision Influenced by Brand Image, and Product Quality in Jayapura City - Khusnul Khotimah; M.Imam Mufti (Publikasi Indonesia, 2024)
This research aims to detect how much influence the brand image and quality of Xiaomi brand mobile products influence consumer purchasing decisions. Research methods use quantitative, qualitative, and associative types of research. The population is all people in Jayapura who buy Xiaomi brand mobile phones, so the number is unknown. The sample amounted to 100 people taken with certain criteria, using purposive proportional random sampling techniques. Tools using SPSS version 26 with multiple linear regression analysis. The results showed a direct relationship between brand image 24.8%, and product quality 26.2%, in the purchase decision of Xiaomi brand mobile phones in the city of Jayapura. While together 24.33%. This means that there is a correlation between brand image and product quality in the purchase decision of Xiaomi brand mobile phones in the city of Jayapura.